2012
DOI: 10.1051/0004-6361/201118750
|View full text |Cite
|
Sign up to set email alerts
|

A brightz= 5.2 lensed submillimeter galaxy in the field of Abell 773

Abstract: During our Herschel Lensing Survey (HLS) of massive galaxy clusters, we have discovered an exceptionally bright source behind the z = 0.22 cluster Abell 773, which appears to be a strongly lensed submillimeter galaxy (SMG) at z = 5.2429. This source is unusual compared to most other lensed sources discovered by Herschel so far, because of its higher submm flux (∼200 mJy at 500 μm) and its high redshift. The dominant lens is a foreground z = 0.63 galaxy, not the cluster itself. The source has a far-infrared (FI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
174
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(182 citation statements)
references
References 50 publications
5
174
1
1
Order By: Relevance
“…Combes et al (2011Combes et al ( , 2012Combes et al ( , 2013, Danielson et al (2011), Fu et al (2012, Sharon et al (2013), Rawle et al (2014), and Magdis et al (2014).…”
Section: Comparison Samplementioning
confidence: 99%
“…Combes et al (2011Combes et al ( , 2012Combes et al ( , 2013, Danielson et al (2011), Fu et al (2012, Sharon et al (2013), Rawle et al (2014), and Magdis et al (2014).…”
Section: Comparison Samplementioning
confidence: 99%
“…This is consistent with our earlier study on LESS J0332 (De Breuck et al 2011), where we estimated that the XDR contribution to the [C ii] 158 μm is ∼1.3%, based on the absorption-corrected X-ray luminosity of L 2−10 keV = 2.5 × 10 44 erg s −1 (Gilli et al 2011) and a scaling relation of L [CII],AGN = 2 × 10 −3 L 2−10 keV (Stacey et al 2010). At high-z [N ii] 205 μm has been detected in HLS J091828.6+514223 at z = 5.24 (Combes et al 2012), APM 08279+5255 at z = 3.91, and MM 18423+5938 at z = 3.93 (Decarli et al 2012). However, their [C ii] 158 μm line has not been observed and consequently their [N ii]/[C ii] ratio is unknown (see Walter et al 2009b, and references therein).…”
Section: Possible Agn Contributionmentioning
confidence: 99%
“…Since the volume ratio of H ii regions and PDRs also depends on cloud properties such as the gas density and ionization structure (hence the ionization parameter), the observed [N ii]/[C ii] flux ratio accordingly depends on those parameters. Recently, [N ii] 205 μm detections have been obtained for three strongly lensed galaxies at z ∼ 4−5 (Decarli et al 2012;Combes et al 2012); however a [C ii] 158 μm detection has not been reported in any of these galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Not much is observationally known about the CO excitation properties of indisputably normal MS galaxies at high redshift. The most detailed information is available for IR-luminous systems selected either as submillimeter galaxies (SMGs; e.g., Bothwell et al 2013;Riechers et al 2013) or strong lenses (Danielson et al 2011;Cox et al 2011;Combes et al 2012;Scott et al 2011;Spilker et al 2014). In a pilot study, Dannerbauer et al (2009) presented CO[3-2] observations of one z = 1.5 galaxy (BzK-21000, further discussed in this paper) that was previously detected in CO[2-1], finding a low CO[3-2]/CO[2-1] ratio fairly consistent with the Milky Way (MW).…”
Section: Introductionmentioning
confidence: 99%